PENDAMPINGAN PELATIHAN "PENGGUNAAN METODE SING A SONG SEBAGAI ALTERNATIF PEMBELAJARAN DALAM PENINGKATAN PENGUASAAN KOSA KATA BAHASA INGGRIS SISWA DI MI AL-IKHSAN CANGA'AN GENTENG" - Nurul Fatimah; Ahmad Izza Muttaqin (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
English as a local content is important and must begin to be taught even though it is still in the operational stage as concrete as in elementary school age children, though only through simple vocabulary recognition. The more someone masters the vocabulary, the more people will be able to speak well and correctly. The fact revealed is that teachers prefer conventional learning with very little use of learning media. To overcome this problem, it is necessary to have a strategy in learning English that encourages and stimulates students to be active in learning, so students want to speak out when they pronounce the vocabulary they say, one of them is the Sing a Song Method. From the results of service that have been done related to the use of the sing a song method as an alternative learning in improving English vocabulary mastery students at MI Al-Ikhsan Canga'an Genteng contributed significantly. After the sing a song method is applied, students tend to be more active and easier to catch new vocabulary, so that the vocabulary of students increases.